HUBUNGAN PERMAINAN TEPUK BEAT TERHADAP KETEPATAN POLA DAN IRAMA ANAK USIA 5-6 TAHUN DI TK ISLAM TERPADU ROBBANI INDRALAYA - Marlianti, Sari; Septiani, Yin Yin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between the clapping beat game and the ability of 5–6 year old children to recognize patterns and rhythms. The clapping beat game is an activity that involves children's movement, hearing, and focus, so it can help the development of their musical abilities. This study used a quantitative approach with a correlational method. The research subjects consisted of 18 children aged 5–6 years at Robbani Indralaya Integrated Islamic Kindergarten. Data collection was carried out through observations using an assessment sheet to evaluate the clapping beat game and the children's ability to recognize patterns and rhythms. Data were analyzed using the Spearman Rank correlation test. The results of the study showed a significant relationship between the clapping beat game and children's ability to understand and follow patterns and rhythms. This finding indicates that children's ability to follow the clapping beat game is related to their ability to recognize and follow patterns and rhythms. This research is expected to provide benefits in enriching music and movement-based learning activities in early childhood education.